Risk factors for denosumab-related osteonecrosis of the jaw: a pharmacovigilance study using the U.S. FDA adverse event reporting system database - Bai, Hehe; Wang, Jinping; Han, Xiaonian; Li, Huan; Nie, Xiaojing; Wang, Guan (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to comprehensively evaluate risk factors for denosumab-related osteonecrosis of the jaw (ONJ), focusing on dosage, concomitant medications, and patient demographics, to inform clinical decision-making and optimize therapeutic strategies.MethodsA retrospective pharmacovigilance analysis was conducted using data from the US FDA Adverse Event Reporting System (FAERS) spanning Q2–2010 to Q3 2024. Disproportionality analysis, logistic regression analysis, and time-to-onset analysis were employed to assess the association between denosumab use and ONJ. Key variables included dosage (60 mg Q6m vs. 120 mg Q4w), concomitant medications (e.g., bisphosphonates, glucocorticoids, chemotherapies), and patient demographics (age, sex).ResultsAmong 7,689 denosumab-related ONJ cases, the 120 mg dose demonstrated markedly higher ONJ risk (reporting odds ratio [ROR] = 245.47 vs. 28.59 for 60 mg; P < 0.001), with a 54-day shorter median onset time (452 vs. 506 days; P = 0.011). Combination therapies synergistically amplified risk, with sequential administration of zoledronic acid yielding the highest ROR at 726.43 (95% CI: 642.83–820.90) and an accelerated time to onset (median 378 days vs. 462 days for monotherapy). Multivariate logistic regression confirmed age ≥65 years (adjusted odds ratio [aOR] = 1.48), high-dose denosumab (aOR = 7.18), and concomitant medications (e.g., bisphosphonates, glucocorticoids, chemotherapies) as independent risk factors. Male patients had a threefold higher risk than females (ROR = 231.11 vs. 51.01), while age showed minimal influence on latency periods (P = 0.808). Weibull analysis demonstrated wear-out failure (β>1) in most subgroups, indicating cumulative toxicity; however, random failure patterns (β≈1) were observed with: 60 mg dosing and either sequential therapies (alendronate/ibandronate/risedronate) or combination therapy with methotrexate.ConclusionsThis study demonstrates that the risk of denosumab-related ONJ is multifactorial, driven by high-dose regimens (120 mg Q4w), specific polypharmacy (particularly concomitant bisphosphonates and glucocorticoids) and male sex. These findings underscore the need for prospective validation and mechanistic investigation into the underlying drug interactions.